The Patient Wants to Withdraw - Whitbeck, Caroline (Online Ethics Center, 2006)
A scenario meant to stimulate discussion about the ethical issues that arise when a patient wishes to withdraw from a clinical study and the researcher disputes the patient's competency.
Open-ended scenario
Keywords: Human Subjects Research; Research and Practice; Vulnerable Populations